Innovative telemonitoring system for cardiology: from science to routine operation - Kastner, P.; Morak, J.; Modre, R.; Kollmann, A.; Ebner, C.; Fruhwald, FM.; Schreier, G. (Applied Clinical Informatics, 2010)
Objective: Results of the Austrian MOBITEL (MOBIle phone based TELemonitoring for heart failure patients) trial indicate that home-based telemonitoring improves outcome of chronic heart failure (CHF) patients and reduces both frequency and duration of hospitalizations. Based on lessons learned, we assessed the weak points to clear the way for routine operations.Methods: We analyzed the system with respect to recommendations of the ESC Guidelines and experiences gained throughout the trial to identify potential improvements. The following components have been identified: a patient terminal with highest usability, integrated way to document drug-intake and well-being, and automated event detection for worsening of CHF. As a consequence the system was extended by Near Field Communication (NFC) technology and by an event management tool.Results: Usability evaluation with 30 adults (14f, median 51y. IQR[45-65]) showed that 21 (8f) were able to immediately operate the system after reading a step-by-step manual. Eight (6f) needed one time demonstration and one man (80y) failed to operate the blood pressure meter. Routine operation of the revised system started in March 2009. Within 9 months, 15 patients (4f, median 74y. IQR[71-83], all NYHA-III) transmitted 17,149 items. 43 events were detected because of body weight gain of more then 2kg within 2 days. 49 therapy adjustments were documented. Three patients stopped using the system, two (1f) because of non-compliance and one (m, 82y) because of death. Overall, the rate of adherence to daily data transfer was 78%.Conclusion: First results confirm the applicability of the revised telemonitoring system in routine operation.Citation: Kastner P, MorakJ, Modre R, Kollmann A, Ebner C, Fruhwald FM, Schreier G. Innovative telemonitoring system for cardiology: from science to routine operation. Appl Clin Inf 2010; 1: 165–176 http://dx.doi.org/10.4338/ACI-2009-12-RA-0021
Keywords: Heart failure; telemedicine; mobile phone; eHealth; near field communication technology